Inter- and intra-firm diffusion of technology: the example of e-commerce:an analysis based on Swiss firm-level data - Heinz Hollenstein; Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2007)
The paper aims at a joint analysis of inter-firm and intra-firm diffusion of technology, taking as an example E-selling and E-purchasing. The analysis is based on an encompassing model of diffusion, drawn from the literature, which is extended by considering technology-specific obstacles and benefits of adoption. As hypothesised, we find, firstly, that the determinants of inter-firm and intrafirm diffusion differ in case of both types of E-commerce; secondly, that the drivers of the diffusion of E-selling and E-purchasing are not the same, and, finally, that uncertainties and adjustment costs, mostly neglected in previous work, are important factors in explaining technology diffusion.
Keywords: O3; 330; Technology diffusion; Inter-firm and Intra-firm diffusion; E-commerce; E-selling; Epurchasing; Technischer Fortschritt; Unternehmensentwicklung; Innovationsdiffusion; Branchenentwicklung; E-Business; Schätzung; Schweiz